Efecto de adición de lipidol® en alimento para pollos de engorde Cobb 500 y su comportamiento sobre sus parámetros productivos - Cedeño Loor, Gladys Marleny (2021)
The purpose of this quantitative study was to evaluate the effect of the inclusion of hydrolyzed soy lecithin (lipidol®) in feed for Cobb 500 broilers, trying to resolve technical limitations related to the profitability of the poultry exploitation process commonly widespread in the region. For this purpose, an experimental trial was implemented using a Completely Randomized Design with a 4x3 factorial arrangement, factor A (lipidol inclusion levels: 0, 0.50; 0.75 and 1.0 kg / T of food) and factor B (periods of use: 1-7; 1-15 and 1-21 days), with 12 treatments and 3 replicates on a total population of 288 chickens. The results indicate that the addition of different doses of hydrolyzed soy lecithin represented the increase in the weekly weight accumulated on chickens with the treatment (1 kg / T + 1-21 days) with 2963.91 grams (P = 0.0001: 5 % significance), daily weight gain (P = 0.0001: 5% significance) with 69.56 grams, accumulated weekly food consumption (P = 0.0001: 5% significance) with 5643.26 grams, a lower percentage of mortality (1.41%) and higher percentage of viability (98.59%). Finally, the cost-benefit analysis shows that the Lipidol® application (1 kg / T + 1-21 days) represents economic benefits in the production of chickens, registering a cost / benefit ratio of 1.15, which means a return 15 cents for every dollar invested.